2020
DOI: 10.1097/won.0000000000000718
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression in Persons With Ostomies

Abstract: PURPOSE: The purpose of this study was to measure the prevalence of anxiety and depression in adults with ostomies and to identify associated factors. DESIGN: A descriptive cross-sectional study. SUBJECTS AND SETTING: The sample comprised 120 adults; all reside in a health region in the state of Minas Gerais in southeastern Brazil. METHODS: Participants responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The total sample size for anxiety related studies was 3394 patients (average 242 patients in each study) and the total sample size in depression related studies was 3821 patients (average 211 patients in each study). The studies were conducted in 12 different countries including United Kingdom, 22,23 Spain, 24 Netherlands, 16 USA, 15,25 Iran, 18,26 Jordan, 27 South Korea, 28,29 Pakistan, 30 Sri Lanka, 5 China, 31 Australia, 32,33 Brazil 17,34 and 5 different regions including Europe, North America, South America, Asia and Oceania. The most used instrument in both variables was the Hospital Anxiety and Depression Scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total sample size for anxiety related studies was 3394 patients (average 242 patients in each study) and the total sample size in depression related studies was 3821 patients (average 211 patients in each study). The studies were conducted in 12 different countries including United Kingdom, 22,23 Spain, 24 Netherlands, 16 USA, 15,25 Iran, 18,26 Jordan, 27 South Korea, 28,29 Pakistan, 30 Sri Lanka, 5 China, 31 Australia, 32,33 Brazil 17,34 and 5 different regions including Europe, North America, South America, Asia and Oceania. The most used instrument in both variables was the Hospital Anxiety and Depression Scale.…”
Section: Resultsmentioning
confidence: 99%
“…15 The prevalence of anxiety and depression in patients with ostomy, respectively, were reported to be 13.4% and 17.5% in US (15), 27.6% and 26.8% in Netherlands 16 and 52.5% and 26.7% in Brazil. 17 Surprisingly, in Iran, a study by Rafiei et al reported that 92.1% of patients with ostomy had experienced some degree of anxiety, and 87% of these patients had experienced some degree of depression. 18 Accurate estimation of the prevalence of depression and anxiety in patients with ostomy is important for prevention, treatment and improved quality of life 11 and can have important consequences for the patient and the health care system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These lesions are often associated with crusts on the stoma and skin related to alkaline urine output. 5,12 In some cases, they have been known to cause hemorrhage and pain. 4,10 Given compromised skin integrity, the cycle of pouch leakage, further skin erosion, and more leakage occurs.…”
Section: Etiology and Incidencementioning
confidence: 99%
“…With a sample size of 120 adults, researchers found that the prevalence of depression was 26.7%, whereas anxiety was 52.5%. 5 Combine the ostomy with a peristomal skin complication, and the mental health impact is magnified.…”
Section: Introductionmentioning
confidence: 99%